Global Trends and Research Clusters in Student Metacognition in Mathematics Education: Tren Global dan Klaster Penelitian Metakognisi Siswa dalam Pendidikan Matematika - Agustina, Sandra; Huda, Nizlel; Sainuddin, Syamsir (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Mathematics education fosters logical and critical thinking, where metacognition—students’ awareness and regulation of their thinking—plays a pivotal role. Specific background: Despite the growing number of studies, a comprehensive mapping of research patterns in student metacognition remains limited. Knowledge gap: Prior works emphasize classroom applications rather than systematic bibliometric visualization. Aims: This study aims to analyze global trends, thematic clusters, and temporal developments in student metacognition research within mathematics education. Results: From 362 Scopus-indexed articles (2015–2025), publication growth is dominated by mathematics (42.2%) and social sciences (41.7%). Keyword mapping identifies four clusters: metacognitive strategies and skills, conceptual frameworks, affective and individual factors, and metacognitive dimensions. Temporal mapping shows a thematic shift from conceptual foundations to technology integration, motivation, and collaboration. Novelty: The study integrates systematic literature review and bibliometric visualization using VOSviewer to provide a holistic picture of metacognition research. Implications: Findings offer insights for educators and researchers to design reflective, self-regulated, and collaborative learning strategies grounded in metacognitive awareness. Highlight Publication trends show increasing attention to metacognition in mathematics learning. Four major research clusters reveal multidimensional themes in metacognitive studies. Recent studies emphasize motivation, technology, and collaboration in metacognition research. Keyword Metacognition, Self-Regulation, Problem Solving, Mathematics Learning, Bibliometric Analysis